Suicidal behaviour in adolescents with affective disorders: A study in a crisis intervention unit (CIU) - José Alejandro Valdevila Figueira; María Alejandra Espinoza de los Monteros Andrade; Rocío Valdevila Santiesteban; Andrés Ramírez; Indira Dayana Carvajal Parra; Jimmy Daniel Martin Delgado; Pedro Carlos Martínez-Suárez; Luis Patricio Benenaula Vargas; María Emilia Andrade Hidalgo; Jose A. Rodas (PLoS ONE, 2025)
Background Suicidal behaviour is a critical mental health issue in the adolescent population, often linked to serious emotional problems that leave survivors vulnerable to future risk. Psychological crises in adolescence are primarily associated with relational conflicts, with emotional crises involving depression or anxiety significantly increasing suicidal risk. Objective This study aimed to evaluate the rates of suicidal behaviour in adolescents undergoing emotional crises and explore their association with psychiatric diagnoses and demographic factors in Ecuador. Methods An observational, correlational study using a quantitative approach was conducted. Data from 252 adolescents admitted to the Crisis Intervention Unit at the Institute of Neurosciences in Guayaquil, Ecuador, between 2011 and 2023 were analysed. Hospitalisation frequencies by year, gender, and associated psychiatric diagnoses were assessed. Data were obtained from each patient’s unified clinical history. Results The study found that suicidal behaviour in adolescents hospitalised for emotional crises was most prevalent among females aged 16–18 years. Depressive episodes were the most common psychiatric diagnosis (73%), and cutting was the most frequent method of self-harm, followed by the ingestion of psychotropic substances. A combination of suicidal ideation and attempts was the most frequent presentation (64%), with family conflicts identified as the main source of distress. Conclusions The high frequency of suicidal behaviour in adolescent females aged 16-18 years underscores the need for targeted prevention programs addressing emotional crises and stress management in this high-risk group.